Lignicolous freshwater fungi from China and Thailand: Multi-gene phylogeny reveals new species and new records in Lophiostomataceae - D. F. Bao (2020)
© 2019, Guizhou Key Laboratory of Agricultural Biotechnology. We are investigating the diversity of lignicolous freshwater fungi from China and Thailand. In this study, six collections of Lophiostomataceae-like taxa were made from freshwater habitats in China and Thailand, of which three are identified as existing species Biappetidiculispora japorrica, Neovaginatispora fuckelii and Vaginatispora armatispora. While, the other collections are recognized as new species, Flabellascorna aquaticum sp. nov., F. fitsiforme sp. nov. and Sigarispora clavata sp. nov. and these are introduced herein based on the morphological characters and multi-gene phylogenetic analyses of combined LSU, SStl ITS, TEFl-a and RPB2 sequence data. Detailed descriptions and illustrations of these six species are provided.